Vehicle-to-grid : linking electric vehicles to the smart grid - Lu, Junwei; Hossain, Jahangir (IET power and energy series, 2015)
Plug-in electric and hybrid vehicles (PEVs) have the potential to provide substantial storage to a city's grid, a key component in mitigating intermittency issues of power sources. But the batteries of these vehicles also need to be charged at times when their users need them. Thus, V2G (vehicle-to-grid) is becoming an important issue in the future grid. An integrated treatment of this system, from power generation, monitoring, storage in stationary and PEV batteries to control is a complex task. This book explores the connection between the stationary grid and PEV power storage. Topics covered include: the impact of PEVs and V2G on smart grid and renewable energy systems; distributed energy resource with PEV battery energy storage in the smart grid; power conversion technology in smart grid and PEVs; power control and monitoring of smart grid with PEVs; PEV charging technologies and V2G on distributed energy resources and utility interfaces; economic, social and environmental dimensions of PEVs in the smart grid. This book will be of interest to researchers and advanced students in electric vehicles and smart grid technologies, and policy-makers and planners developing smart grid infrastructure and sustainable transport initiatives.